The economics of art and culture - Heilbrun, James 1924-; Gray, Charles M. (Cambridge University Press, 2001)
The 2001 second edition of this survey of the economics of - and public policy towards - the fine arts and performing arts covers arts at federal, state, and local levels in the United States as well as the international arts sector. The work will interest academic readers in the field and scholars of the sociology of the arts, as well as general readers seeking a systematic analysis of the arts. Theoretical concepts are developed from scratch so that readers with no background in economics can follow the argument. The authors look at the arts' historical growth and then examine consumption and production of the live performing arts and the fine arts, the functioning of arts markets, the financial problems of performing arts companies and museums, and the key role of public policy. A final chapter speculates about the future of art and culture in the United States
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Arts / Economic aspects / United States; Kunstpolitik; Kunstmarkt; USA; United States / Cultural policy